Makna âSeneng lan Kemringetâ dalam Festival Lima Gunung - Aswoyo, Joko; Rustopo, Rustopo; Simatupang, Lono Lastoro; Kartono, Drajat Tri (PANGGUNG, 2018)
ABSTRACTThis article aims to discover the meaning of the expression âseneng lan kemringetâ at FLG (Festival Lima Gunung) in Magelang. The expression âseneng lan kemringetâ gives an opportunity to anybody who involved to reveal his existence and to speak about the essence of himself. By building a sense of familiarity, direct involvement in art activities, and dialogue with the farmers about circumstances in the field, it will be possible to reveal the meaning behind the expression âseneng lan kemringet. The research results showed that within the expression seneng lan kemringet, there is vitality as a fundamental asset for the FLG sustainability. âSeneng lan kemringetâ can also be understood as an autonomy and self-actualization. Additionally, seneng lan kemringet is a part of a game with the goal of displaying self-existence. Finally, âseneng lan kemringetâ is an embodiment of self-esteem.Â Keywords: âseneng lan kemringetâ, vitality, and gameÂ ABSTRAKArtikel ini bertujuan untuk mengetahui makna ungkapan âseneng lan kemringetâ pada Festival Lima Gunung (FLG) di Magelang. Ungkapan âseneng lan kemringetâ memberi kesempatan bagi yang terlibat untuk mengungkapkan keberadaannya dan berbicara tentang hakikat dirinya. Dengan keakraban, keterlibatan langsung dalam aktivitas kesenian, dan berdialog dengan petani atas kenyataan-kenyataan di lapangan, akan dapat disingkap makna di balik ungkapan âseneng lan kemringetâ tersebut. Hasil dari penelitian kami menunjukkan bahwa di dalam ungkapan âseneng lan kemringetâ tersimpan daya hidup sebagai modal dasar keberlanjutan FLG. âSeneng lan kemringetâ juga dimaknai sebagai otonomi dan aktualisasidiri. Selain itu, âseneng lan kemringetâ adalah bagian dari permainan dengan tujuan untuk memperlihatkan eksistensi diri. Pada akhirnya, âseneng lan kemringetâ merupakan kebanggaan diri.Kata kunci: âseneng lan kemringetâ, daya hidup, dan permainanÂ